Indenter size effect on the reversible incipient plasticity of Al (001) surface: Quasicontinuum study*Project supported by the National Natural Science Foundation of China (Grant No. 51172040), the National Basic Research Program of China (Grant No. 2011CB606403), and the General Project of Scientific Research from Liaoning Educational Committee, China (Grant No. L2014135). (August 2015) - Tang, Dan; Shao, Yu-Fei; Li, Jiu-Hui; Zhao, Xing; Qi, Yang
Abstract Indenter size effect on the reversible incipient plasticity of Al (001) surface is studied by quasicontinuum simulations. Results show that the incipient plasticity under small indenter, the radius of which is less than ten nanometers, is dominated by a simple planar fault defect that can be fully removed after withdrawal of the indenter; otherwise, irreversible incipient plastic deformation driven by a complex dislocation activity is preferred, and the debris of deformation twins, dislocations, and stacking fault ribbons still remain beneath the surface when the indenter has been completely retracted. Based on stress distributions calculated at an atomic level, the reason why the dislocation burst instead of a simple fault ribbon is observed under a large indenter is the release of the intensely accumulated shear stress. Finally, the critical load analysis implies that there exists a reversible-irreversible transition of incipient plasticity induced by indenter size. Our findings provide a further insight into the incipient surface plasticity of face-centered-cubic metals in nano-sized contact issues.